Manta-like planktivorous sharks in Late Cretaceous oceans - Vullo, Romain; Frey, Eberhard; Ifrim, Christina; González, Margarito A. González; Stinnesbeck, Eva S.; Stinnesbeck, Wolfgang (Science, 2021)
The ecomorphological diversity of extinct elasmobranchs is incompletely known. Here, we describe Aquilolamna milarcae, a bizarre probable planktivorous shark from early Late Cretaceous open marine deposits in Mexico. Aquilolamna, tentatively assigned to Lamniformes, is characterized by hypertrophied, slender pectoral fins. This previously unknown body plan represents an unexpected evolutionary experimentation with underwater flight among sharks, more than 30 million years before the rise of manta and devil rays (Mobulidae), and shows that winglike pectoral fins have evolved independently in two distantly related clades of filter-feeding elasmobranchs. This newly described group of highly specialized long-winged sharks (Aquilolamnidae) displays an aquilopelagic-like ecomorphotype and may have occupied, in late Mesozoic seas, the ecological niche filled by mobulids and other batoids after the Cretaceous-Paleogene boundary.